2007
DOI: 10.1021/bi700944j
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Specific Interactions of the Fibrinogen αC-Domains with the Central E Region and with Each Other

Abstract: The carboxyl-terminal regions of the fibrinogen Aα chains (αC regions) form compact αC-domains tethered to the bulk of the molecule with flexible αC-connectors. It was hypothesized that in fibrinogen two αC-domains interact intramolecularly with each other and with the central E region preferentially through its N-termini of Bβ chains, and that removal of fibrinopeptides A and B upon fibrin assembly results in dissociation of the αC regions and their switch to intermolecular interactions. To test this hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 73 publications
7
119
0
Order By: Relevance
“…The binding sites within the ␣C regions involved in the interactions with fibrinopeptides and self-association have not been established. Nevertheless, the ability of the fragments representing the entire ␣C region or the ␣C domain to form oligomers, as well as the reports of ␣C-␣C interactions at the single-molecule level provide direct evidence that they contain the self-association sites (19,33). The release of fibrinopeptides B by thrombin during the conversion of fibrinogen to fibrin is accompanied by the dissociation of the ␣C regions from the E region (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The binding sites within the ␣C regions involved in the interactions with fibrinopeptides and self-association have not been established. Nevertheless, the ability of the fragments representing the entire ␣C region or the ␣C domain to form oligomers, as well as the reports of ␣C-␣C interactions at the single-molecule level provide direct evidence that they contain the self-association sites (19,33). The release of fibrinopeptides B by thrombin during the conversion of fibrinogen to fibrin is accompanied by the dissociation of the ␣C regions from the E region (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…8A). The interaction of the ␣C regions with the E region is mediated mainly via fibrinopeptides B, although the contribution of fibrinopeptides A has also been shown (19). The binding sites within the ␣C regions involved in the interactions with fibrinopeptides and self-association have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since the region contains the β-wall to which thrombin binds [17], FpA release is likely to be impaired. Besides, the deletion of Bβ9-72 could affect the function of αC domain, because FpA is involved in the interaction with αC domain together with BβN region [11]. Thus, the deletion of Bβ9-72 results in not only the impaired function of BβN region, but also affects the release of αC-domain.…”
Section:  mentioning
confidence: 99%
“…Bowley and Lord have reported that b-hole and binding between B-knob and b-hole per se have no influence on fibrin polymerization [10]. Because the interaction between the αC-domain and central E region through FpB and the interaction between αC-domains have been ascertained [11], the importance of the αC-domain is clear, but another substantial factor for polymerization should be involved especially in the lateral aggregation process.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to fibrin polymerization, the αC region is tethered to the central E region. 30,31 Fibrinogen is converted to active fibrin upon thrombin cleavage of fibrinopeptides A and B, on the Aα and Bβ chains respectively. Cleavage of fibrinopeptides A and B initiates fibrin polymerization by exposing knobs "a" and "b" in the central E region which interact with the complementary holes "A" and "B" in the D region of another fibrin molecule.…”
Section: -30mentioning
confidence: 99%